Identification of Key Success Factors in the Marketing of Cosmetics Based on Knowledge, Attitude and Practice (KAP) Analysis Using Topsis Technique (The Case of Iran) - Mehdi Mohammadzadeh, Shirin Hashemi, Faranak Salmannejad, Tayebeh Ghari (Tabriz University of Medical Sciences, 2017)
Background: Cosmetic products are one of the most important fields of consumer market. Strategic marketing plan and creating competitive advantages through recognizing of key success factors has become as a main core competency of active firms in this area. Based on this, the aim of our study was to identify the key success factors of cosmetic products' marketing in the Iran's market. Methods: To do this, knowledge, attitude, and practice (KAP) of consumers in Iran were evaluated and key success factors were identified based on the mix marketing theory. Deep interviews and closed-ended questionnaires were used to collect data. The randomized sample population of this study was 1200 people. Results of KAP analysis were classified in seven clusters and then Topsis technique was used to analysis each cluster. Results: Results showed that there are a significant relationship between attitude and practice and also between knowledge and practice because of t-values greater than 1.96 and path coefficient greater than 0.1. Moreover, the results indicated that the most and the least important factors for success of cosmetics' marketing are place (distribution and dispensing) and price, with sorted Cli of 0.9 and 0.1 respectively. Conclusion: It demonstrates that appropriate sales and distribution strategies, scientific and enough information and strong marketing at the point of purchase are the most important key success factors in the marketing of cosmetics, and price has a minimum drawing effect on cosmetics' marketing.